Nursing home-acquired pneumonia: a 10 year single-centre experience. Issue 4 (13th April 2010) - Polverino, E; Dambrava, P; Cillóniz, C; Balasso, V; Marcos, M A; Esquinas, C; Mensa, J; Ewig, S; Torres, A
Abstract : Background: Pneumonia among nursing home (NH) residents has increased considerably in recent years, but it remains unclear whether it should be considered as community-acquired pneumonia (CAP) or a new category of infection. Methods: 150 consecutive cases of NH-acquired pneumonia (NHAP) (from 1 February 1997 to 1 July 2007) were analysed. Results: Patients (median age, 82 years; range, 77–87 years) showed numerous co-morbidities, (neurological, 55%; pulmonary, 38%; cardiac, 35%) and severe disability for daily activities (partial, 32%; total, 31%). Cases of NHAP were mainly classified as mild to moderate according to the CRB-65 score (CRB-65 classes 0–1 and 2, 41% each). In-hospital and 30-day mortality were 8.7% and 20%, respectively. Aetiology was defined in 57 cases (38%). The most common isolates were Streptococcus pneumoniae (58%), Enterobacteriaceae (Gram-negative bacteria (GNB)) (9%), atypical bacteria (7%), respiratory viruses (5%), methicillin-resistant Staphylococcus aureus (MRSA) (5%) and Legionella pneumophila (5%). The most frequent causes of treatment inadequacy were use of β-lactams alone (25%) and lack of aspiration assessment (15%). Prognostic factors of 1-month mortality were neurological comorbidities (OR 4.5; 95% CI 1.3 to 15.7; p=0.020), septic shock (OR 6.6; 95% CI 1.3 to 34.0; p=0.025), pleural effusion (OR 3.6; 95% CI 1.1 to 11.7; p=0.036) and isolation of GNB or MRSA (OR 16.4; 95% CI 2.1 to 128.9; p=0.008). Conclusions: The patients show clinical characteristics (eg, age and co-morbidities) comparable with those with hospital-acquired pneumonia. However, microbiological and mortality data of patients with NHAP are more similar to the data of those with CAP. Isolation of GNB or MRSA was associated with increased mortality risk. CAP empirical antibiotic coverage is still indicated in NHAP, although specific risk factors for multidrug-resistant infections should be assessed on an individual basis.